Microstructure and Selective Corrosion of Alloy 625 Obtained by Means of Laser Powder Bed Fusion - Cabrini, Marina (Materials (Basel), 2019)
The effect of microstructure on the susceptibility to selective corrosion of Alloy 625 produced by laser powder bed fusion (LPBF) process was investigated through intergranular corrosion tests according to ASTM G28 standard. The effect of heat treatment on selective corrosion susceptibility was also evaluated. The behavior was compared to commercial hot-worked, heat treated Grade 1 Alloy 625. The morphology of attack after boiling ferric sulfate-sulfuric acid test according to ASTM G28 standard is less penetrating for LPBF 625 alloy compared to hot-worked and heat-treated alloy both in as-built condition and after heat treatment. The different attack morphology can be ascribed to the oversaturation of the alloying elements in the nickel austenitic matrix obtained due to the very high cooling rate. On as-built specimens, a shallow selective attack of the border of the melt pools was observed, which disappeared after the heat treatment. The results confirmed similar intergranular corrosion susceptibility, but different corrosion morphologies were detected. The results are discussed in relation to the unique microstructures of LPBF manufactured alloys.